Hubungan Konsumsi Minuman Manis dengan Kejadian Diabetes Melitus pada Remaja Perempuan - Christy, Arisa Angelia; Tjomiadi, Cynthia Eka Fayuning; Asmadiannor, Asmadiannor; Syahlani, Ahmad (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Diabetes mellitus, with a global prevalence of 10.5% in 2021 and projected to reach 12.2% by 2045, particularly in middle-income countries, recorded 2,866 cases in Banjarmasin in 2023, with a significant increase among adolescents, including a 70 fold rise in cases among children since 2010. High-sugar beverage consumption, such as soda and packaged juices, elevates the risk of obesity and diabetes in adolescent girls due to hormonal factors, leading to complications like hypoglycemia, hyperglycemia, retinopathy, nephropathy, and heart disease, with observations at Puskesmas S. Parman Banjarmasin indicating daily consumption of sugary drinks linked to obesity and prediabetes symptoms. To analyze the relationship between the habit of consuming sugary drinks and the incidence of diabetes mellitus among adolescent girls in the working area of Puskesmas S. Parman, Banjarmasin. This study employed a quantitative method with a cross-sectional design, involving 83 adolescents in the Puskesmas S. Parman area, Banjarmasin, selected through purposive sampling. Data were collected using the SQ-FFQ questionnaire and digital glucometer, then analyzed univariately and bivariately with chi-square tests and Odds Ratio. This study found that 42.16% of 83 respondents had a high habit of consuming sugary drinks and exhibited symptoms of elevated blood sugar levels. Statistical test results indicated a significant relationship between the habit of consuming sugary drinks and the incidence of diabetes mellitus in adolescents (p < 0.05). Frequent consumption of sugary drinks among adolescent females, is significantly correlated with a higher risk of diabetes mellitus and elevated blood sugar levels.